Consumption patterns of neglected and underutilized species by households and associated factors in Atacora, Northern Benin - Bankole, Bissola (2023)
Presented at the Doctoriales of University of Abomey-Calavi, September 2023, Abomey-Calavi, Benin. This presentation highlights the results of an evaluation on the consumption level of Adansonia digitata, Ocimum gratissimum, Vigna radiata, and Moringa oleifera as well as the factors associated to their consumption by households, especially women of childbearing age and children aged 6-23 months in Northern Benin.